Integrated Fecal Microbiome and Serum Metabolomics Analysis Reveals Abnormal Changes in Rats with Immunoglobulin A Nephropathy and the Intervention Effect of Zhen Wu Tang - Li, Jicheng; Cao, Yiwen; Lu, Ruirui; Li, Honglian; Pang, Yu; Fu, Hongxin; Fang, Guoxing; Chen, Qiuhe; Liu, Bihao; Wu, Junbiao; Zhou, Yuan; Zhou, Jiuyao (Frontiers in Pharmacology, 2021)
Immunoglobulin A nephropathy (IgAN), an autoimmune renal disease with complicated pathogenesis, is one of the principal reasons for end-stage renal disease in the clinic. Evidence has linked apparent alterations in the components of the microbiome and metabolome to renal disease in rats. However, thus far, there is insufficient evidence that supports the potential relationship between gut microbiome, circulating metabolites, and IgAN. This study was designed to probe the effects of IgAN on intestinal microecology and metabolic phenotypes and to understand the possible underlying mechanisms. Fecal and serum samples were collected from IgAN rats. Composition of the gut microbiota and biochemical changes in the metabolites were analyzed using 16S rDNA sequencing and untargeted metabolomics. The IgAN rats exhibited renal insufficiency and increased concentration of 24h urine protein, in addition to deposition of IgA and IgG immune complexes in the kidney tissues. There was a disturbance in the balance of gut microbiota in IgAN rats, which was remarkably associated with renal damage. Marked changes in microbial structure and function were accompanied by apparent alterations in 1403 serum metabolites, associated with the disorder of energy, carbohydrate, and nucleotide metabolisms. Administration of Zhen Wu Tang (ZWT) ameliorated microbial dysbiosis and attenuated the renal damage. Besides, treatment with ZWT modulated the metabolic phenotype perturbation in case of gut microbiota dysbiosis in IgAN rats. In conclusion, these findings provided a comprehensive understanding of the potential relationship between the intestinal microbiota and metabolic phenotypes in rats with IgAN. Elucidation of the intestinal microbiota composition and metabolic signature alterations could identify predictive biomarkers for disease diagnosis and progression, which might contribute to providing therapeutic strategies for IgAN.